Reflection in practice as source of values: the cross-cultural creation of a health-care ethic in post-Apartheid South Africa - Shutte, Augustine (Journal for the study of religion, 2018)
As a starting-point, in his well-known definition of a practice', Alasdair MacIntyre argues that the reflection' involved in practice', is best understood as a dialogue between different partners, whether individuals or groups. Such reflection, aimed as it is at the achievement of excellence in the practice concerned, can (if pursued with rigour and commitment), uncover values embedded in the practice which, however limited the practice (rugby, gardening), have a wider, even universal, scope. When the partners in dialogue have general recognition of one another (religions, countries, professional bodies, political parties), these values can provide materials for a Global Ethic (Parliament of the World's Religions), that is constructed from the bottom up (the Oregon Plan), rather than by some public authority (the United Nations). This article provides grounds for this view by examining the practice of health-care in post-apartheid South Africa, and the co-reflection of scientific health-care professionals and traditional healers, that are part of constructing a new model for health-care that better serves the needs of all South Africans. This dialogue may uncover values whose scope is wider than that of health-care and which could provide a really humane foundation for a society containing different cultures.Keywords: practice, Alisdair MacIntyre, reflection, values, culture/s, ethic, health-care professionals, traditional healers